Brainstorming the New Avenues for Translational Proteomics Research: First Indo-US Bilateral Proteomics Workshop - Ray, Sandipan; Bhave, Amruta; Srivastava, Sanjeeva (Current Proteomics, 2015)
During beginning of the twenty first century the rapidly emerged field “Proteomics” showed diverse potential applications in different aspects of clinical research. However, if we retrospect the progress of proteomics research over the last decade without a prejudice, it would be apparent that there is a serious bottleneck between the promising laboratory findings and their successful translation in real clinical applications. To this end, during the last December (2014) we conducted the first Indo-US Bilateral Proteomics Workshop in order to bring the leading proteomics scientists from India and USA in a round table discussion addressing the prospects and challenges of translational proteomics research. This one- day workshop entitled “Proteomics for Translational Research” was organized at the Indian Institute of Technology Bombay, Mumbai. Dr. Sanjeeva Srivastava from the Indian Institute of Technology Bombay, India and Dr. Philip Andrews from the University of Michigan, USA served as the joint coordinators for this scientific event. The recent advancements in proteomic technologies and their feasible uses in translational research were discussed in this scientific event, with a focus on the existing challenges and amenable solutions. Of note, this bilateral event witnessed participation of the most prominent scientists involved in the path breaking research ventures in the field of proteomics, and also many of the pioneers of the Human Proteome Organization (HUPO). This Indo-US bilateral workshop may set up an alleyway for enduring collaborative research and educational programs among the scientists/ institutes from these two countries in the upcoming future.
Keywords: Translational Research